AN ANALYSIS OF FORMATIVE AND SUMMATIVE ASSESSMENT BY ENGLISH FOREIGN LANGUAGE (EFL) TEACHER - Listiani, Fittrizah; Nasrullah (Universitas Negeri Manado, 2023)
This article discusses the significance of assessment in English language education and its role in improving learning quality and student motivation. The implementation of formative and summative assessments is explored, highlighting their differences and benefits. The article emphasizes the importance of understanding and employing these assessment types, particularly for English as a Foreign Language (EFL) teachers. The findings and discussion section delves into the implementation of formative and summative assessments in English classrooms, including strategies employed and their effects on student learning. The conclusion underscores the significance of both assessment types in English language education, emphasizing their ability to provide valuable insights into student progress, tailor instruction, and foster an engaging learning environment. The article concludes by emphasizing the importance of recognizing the purpose and applicability of formative and summative assessments and their role in enhancing student learning outcomes